Urgency of Quality Concepts and Total Quality Management (TQM) in Islamic Education Institutions - Nurul Mukarromah; Istikomah Istikomah; Eni Fariyatul Fahyuni (Proceedings of The ICECRS, 2020)
Total quality Management (TQM) is a form of organization management approach that emphasizes quality, with the aim of achieving success in the long run, as well as providing satisfaction to its customers. This paper aims to provide an illustration that the management of an educational institution requires the concept of integrated quality management in an effort to develop strategies to achieve organizational goals maximally. Because in this quality management there is a mature, measurable and realistic planning concept in accordance with the available resources. Educational institutions as institutions whose outside targets are in the form of increased human resources with complex aspects, namely intellectual, emotional and spiritual. Clearly it really needs the concept of Total Quality Management in an effort to produce graduation in accordance with the vision and mission of national education objectives. This study is a library research, so that the main data sources are books, journals and other reading sources. Its conclusion is that educational institutions as institutions that create human resources. It is said to be successful if implementing the concept of Total Quality Management with the main objective on customer satisfaction, namely students, parents, community, nation and country. As for the main movers are the principal with all other personnels in that institution the education.